IJIEM Reaches New Heights in Journal Ranking - Marjanovic, Ugljesa (International Journal of Industrial Engineering and Management, 2024)
After five years serving as an Editor-in-Chief for the International Journal of Industrial Engineering and Management (IJIEM), I am delighted to announce that the IJIEM journal has reached significant new heights in the realm of academic publishing. The latest Journal Citation Reports from 2024 have placed IJIEM journal among the top 50% of journals in the Engineering, Industrial category, classifying us within the prestigious Q2 quartile. Our Journal Impact Factor now stands at an impressive 2.4, a testament to the quality and relevance of the research we publish. In addition to this achievement, the 2023 Scopus CiteScore has been released, and I am thrilled to report an outstanding CiteScore of 5.0. This remarkable score places IJIEM journal in the top tier (Q1) of journals, underscoring our journal’s influence and prominence in the academic community. Our journal has also received new rankings in the category of Management Science and Operations Research, further cementing our reputation as a leading publication in these critical fields.